SISTEM PEMESANAN JASA FOTOGRAFI BERBASIS ANDROID DI STUDIO SELAWE BONTANG - Junaini Junaini (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2020)
Selawe Bontang Studio is one of the businesses in the field of services that serve wedding photo services (prewedding), and other events that require documentation. Ordering through social media such as Facebook, Short Message Service (SMS), and WhatsApp (WA), with the problem of limited information, time, transactions, data processing, and payment transactions that have not provided maximum service for customers. The purpose of this study is to create an Android-based photography service ordering system application at Selawe Bontang Studio, which can be installed on a cellphone / smartphone and facilitates ordering and obtaining information. Make maximum use of mobile phones / smartphones with the Photography Services Booking System application made with the Android Studio application, Javascript, PHP, HTML CSS as well as MySql databases solve the problem in Selawe Bontang Studio. The Android-based Photography Services ordering system also impacts on increasing the number of customers and increasing the efficiency and effectiveness of performance at Selawe Bontang Studio.